Coping strategies to stress about emotional intelligence in children 7 to 12 years of disaster victims - Echevarria R., Luis (2012)
This research examines the relationship between stress coping strategies and emotional intelligence in a sample of 227 child victims of disaster, of both sexes, ages 7 to 12 years of age. To establish the relationship between these variables using correlational design, in both data collection was applied Coping Strategies Scale Stress in Children, the same that was created by the researcher, whose validity was established by the criterion of judges and reliability through internal analysis which yielded a Cronbach alpha of .787 for the Coping Strategy Focused on the Problem and .696 for the Coping Strategy Focused on Emotion, likewise, we used the Inventory ICE BarOn Emotional Intelligence: NA, it was adapted and standardized for a sample limeña Ugarriza and Pajarez (2003). The results of correlation analysis of Spearman Rho, indicated a statistically significant relationship between stress coping strategies focused on the problem and total emotional quotient, with the same .36 (p <.01), likewise, found a significant relationship between the moderate and coping strategies focused on emotion and emotional quotient total, with a correlation of 0.41 (p <.01).